Identification of Compounds That Prolong Type I Interferon Signaling as Potential Vaccine Adjuvants. (October 2018) - Shukla, Nikunj M.; Arimoto, Kei-Ichiro; Yao, Shiyin; Fan, Jun-Bao; Zhang, Yue; Sato-Kaneko, Fumi; Lao, Fitzgerald S.; Hosoya, Tadashi; Messer, Karen; Pu, Minya; Cottam, Howard B.; Carson, Dennis A.; et al.
Vaccines are reliant on adjuvants to enhance the immune stimulus, and type I interferons (IFNs) have been shown to be beneficial in augmenting this response. We were interested in identifying compounds that would sustain activation of an endogenous type I IFN response as a co-adjuvant. We began with generation of a human monocytic THP-1 cell line with an IFN-stimulated response element (ISRE)-β-lactamase reporter construct for high-throughput screening. Pilot studies were performed to optimize the parameters and conditions for this cell-based Förster resonance energy transfer (FRET) reporter assay for sustaining an IFN-α-induced ISRE activation signal. These conditions were confirmed in an initial pilot screen, followed by the main screen for evaluating prolongation of an IFN-α-induced ISRE activation signal at 16 h. Hit compounds were identified using a structure enrichment strategy based on chemoinformatic clustering and a naïve "Top X" approach. A select list of confirmed hits was then evaluated for toxicity and the ability to sustain IFN activity by gene and protein expression. Finally, for proof of concept, a panel of compounds was used to immunize mice as co-adjuvant with a model antigen and an IFN-inducing Toll-like receptor 4 agonist, lipopolysaccharide, as an adjuvant. Selected compounds significantly augmented antigen-specific immunoglobulin responses.